Mastery of pMDI technique, asthma control and quality-of-life of children with asthma: A randomized controlled study comparing two inhaler technique training approaches. (April 2017) - Ammari, Wesam G.; Al-Hyari, Nussaibah; Obeidat, Nathir; Khater, Mona; Sabouba, Amal; Sanders, Mark
Abstract: Objective: Verbal counselling (VC) is the clinical standard for training patients on correct inhaler use. Patients fail to recall their VC with time. Ethical approval was obtained to compare the pressurized metered dose inhaler (pMDI) VC with Trainhaler (TH), a novel pMDI inhalation flow and technique training device, in children with asthma. Methods: At visit 1, 7–17 year-old children with a pMDI hand-lung coordination problem including a fast peak inhalation flow (PIF) through pMDI >60 L/min were randomized into either VC group that received verbal pMDI training; or into TH group that were trained on- and given TH to practice at home. Whereas, children with correct pMDI use formed the control group (CT). Overall pMDI technique, PIF through inhaler, asthma control (AC) and quality of life (QoL) were evaluated. Participants were re-evaluated 6–8 weeks later (visit 2). Results: Of 105 enrolled children; 76 completed the study (VC = 21, TH = 25 and CT = 30). VC decreased non-significantly (p > 0.05) the mean PIF from 104.0 L/min at visit 1 to 84.8 at visit 2. Whilst, the TH did significantly (p < 0.05) reduce the PIF from 113.5 to 71.4 L/min. The two approaches similarly and significantly (p < 0.05) improved the inhaler technique, AC and QoL scores. Conclusions: The TH improved the inhalation flow through the pMDI close to the ideal needed for adequate lung deposition. Both methods equally enhanced the children's mastery of pMDI use. This was reflected on better AC and QoL. Accessibility to TH might help maintaining the good inhaler use and decreasing regular VC.